TI_GERICHTE 12.2014.158 vom 26. Mai 2015 , Mediazione immobiliare, cessione di credito, provvigione del mediatore - TI Tribunale d'appello (2015)
Mediazione immobiliare, cessione di credito, provvigione del mediatore